2011
DOI: 10.1007/s10995-011-0885-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Discontinuing Breastfeeding in Southern Brazil: A Survival Analysis

Abstract: To identify risk factors for discontinuing breastfeeding during an infant's first year of life. A cohort study recruited mothers in a hospital in São Leopoldo, Brazil, which mainly serves the low-income population. In order to obtain socioeconomic, environmental, and behavioral information, face-to-face interviews with mothers were conducted after birth, and when their infants were 6 and 12 months old. The duration of breastfeeding was investigated at 6 and 12 months, and recorded separately for each month. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
2
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 41 publications
8
37
2
6
Order By: Relevance
“…Confirming previous studies 7,25 , the precocious introduction of the bottle was a risk factor for weaning in the population studied. Children who use the bottle are more prone to the interruption of breastfeeding and the introduction of new foods in the diet 25 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Confirming previous studies 7,25 , the precocious introduction of the bottle was a risk factor for weaning in the population studied. Children who use the bottle are more prone to the interruption of breastfeeding and the introduction of new foods in the diet 25 .…”
Section: Discussionsupporting
confidence: 89%
“…At 6 months of age, the cumulative probability of breastfeeding was 54.9%, the approximate value of the prevalence found in a 2012 study conducted in the state of Rio Grande do Sul (56.4%) 7 . Contrasted to the results of the present study, a 2009 study performed in Curitiba with children from low-income families showed that 54.2% of children up to 2 years of age were still being breastfed 15 .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…A negative correlation between the use of a dummy and successful breastfeeding was found in all 14 studies 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47 published between 1999 and 2012 (Table 3). …”
Section: Resultsmentioning
confidence: 89%